Performing Allah's work: experiences of Muslim family carers in Britain - Buckman, Sarah K.N. (2011)
This thesis explores how Muslim family carers of chronically ill or disabled family members in Britain perceive, perform and negotiate their caring role. Drawing on data collected from forty-three semi-structured interviews, this thesis shows that although Muslim family carers are not a homogenous group; perceptions, performances and negotiations of care within the family are often mediated through a Muslim religious lens. This manifests itself in three predominant ways explored in this thesis. Firstly, Muslim religious beliefs act as a "sacred canopy" through which carers draw comfort and spiritual meaning for both their caring role and the illness and disability of the cared for relative. Secondly, certain state services are deemed as particularly problematic for upholding Muslim religious identities. Whilst health services are positively received, social services often are deemed as "dangerous" and potentially threatening to family honour (izzat). This is particularly pertinent for carers of females with learning disabilities. Thirdly, Muslim religious and cultural beliefs maintain traditional gendered perceptions of caregiving within the family, often with very little support from outside organisations. This thesis also argues that Muslim carer support organisations use interesting and innovative methods of engaging Muslim family carers as a form of "bridging social capital" to health and social services.